Interfacial bond behaviour of GFRP bar in self-compacting fiber reinforced concrete - Mazaheripour, H. (2012)
In an ongoing research project, discrete steel fibers are being used in a self-compacting concrete (SFRSCC) to replace completely steel stirrups for pre-fabricated beams reinforced longitudinally with pre-stressed glass fiber reinforced polymer (GFRP) and steel bars. To take the advantages of the non-corrodible character and high tensile strength of GFRP bars, the minimum SFRSCC cover needs to be determined in order to assure the adequate bond performance between these bars and the surrounding SFRSCC. Since bond of the longitudinal bars has a relevant impact on the cracking behavior of RC elements (crack opening and crack spacing), an extensive experimental program composed of pullout bending tests was carried out where the influence of the following parameters was assessed in terms of bond behavior: GFRP bar diameter, surface characteristics of the GFRP bars, bond length, SFRSCC cover thickness. The local bond law was derived from inverse analysis and it was used to define the slip mode of the constitutive law adopted for interface finite elements. These interface finite elements were used to assess the crack opening and crack spacing on SFRSCC beams flexurally reinforced with GFRP bars. This paper resumes the experimental program, describes the strategy to derive the local bond law and presents and discusses the numerical simulations.